16. The Number Of Leukocyte And Leukocyte Differential In Broilers That Infected With Eimeria tenella And Given Neem Leaf Extract And Jaloh Extract - Rizki Aulia; Sugito Sugito; M. Hasan; T. Fadrial Karmil; Gholib Gholib; Rinidar Rinidar (Jurnal Medika Veterinaria, 2017)
The aim of this research was to determine the effect of giving neem leaf extract combined with jaloh towards the total of leukocytes and differential leukocyte in broilers that was infected with Eimeria tenella. This research samples were 20 Cobb stain broilers 14 days old. Design the research was complete randomized design with five treatments and each treatment consists of four repetitions. First treatment (P1) as negative control which was only given mineral water; second treatment (P2) as positive control was is given 5 mg/L anti-stress commercial in drinking water; Third treatment (P3) was given 1000 mg/L Jaloh extract; Fourth treatment (P4)was given 250mg/L neem extract; and fifth treatment (P5)was given 1000mg/L jaloh extract combined with 250mg/L neem extract. Anti-stress commercial and extract treatment dissolved in drinking water. The treatment start from 08.00 until 18.00 for ten days. Next in the 11th day (chicken 25 days old)was inoculated Eimeria tanella sporulatif as much as 1 x 104 ookista/ml orally. Then the blood was taken sampling when the chicken 30 days old (five days after infected). Blood sampling was done in the brachial vein. Furthermore, the number of leukocytes and differential leukocyte.Was calculated data were analyzed using complete randomized design with the help of SPSS for Windows 1.8 program. The result of this research showed that giving jaloh and neem leaf extract were not giving significant effect (P0,05) towards the number of leukocyte as well as differential leukocyte of broilers that was infected with Eimeria tenella. The conclusion of this research were giving jaloh leaf extract and neem for 10 days was not giving significant effect towards number of leukocytes and differential leukocyte broilers that infected with Eimeria tenella